Effects of Job Accessibility Improved by Public Transport System: Natural Experimental Evidence from the Copenhagen Metro - Pons Rotger, Gabriel; Sick Nielsen, Thomas (European Journal of Transport and Infrastructure Research, 2015)
This study examines the effect of accessibility to urban jobs via a public transport system on individual earnings and commuting behaviour. The effect of improved public transport based accessibility on these outcomes is determined by exploiting the exogenous variation in access to a public rail and Metro system resulting from the construction of a new terminal Metro station connecting southern townships to Copenhagen city centre. The results show that public transport based job accessibility has a positive and permanent effect on individual earnings. The increase in earnings is associated with a change in commuting patterns as the improved access to public transport facilitates a shift from employment within the township to better paid jobs in the city centre, as well as in other suburbs of the Copenhagen Metropolitan area.